Identification and characterization of polymorphic microsatellite loci in the blue shark Prionace glauca , and cross‐amplification in other shark species - F. F. Mendonça; L. H. F. Ussami; D. T. Hashimoto; L. H. G. Pereira; F. Porto‐Foresti; C. Oliveira; O. B. F. Gadig; F. Foresti (Journal of Fish Biology, 2012)
Two to 14 alleles were found to be segregating per locus (mean 5·2), with observed and expected heterozygosities ranging from 0·08 to 0·78 and 0·08 to 0·94, respectively. Cross‐amplification of six of these microsatellite loci indicated that they are also polymorphic in three species of Carcharhiniformes and two species of Lamniformes. The newly developed primers reported here constitute a useful tool for genetic population analyses on Prionace glauca and, potentially, other related species.